The OCCUPATIONAL HEALTH AND SAFETY (K3) RISK ANALYSIS USING HIRADC AND JSA METHODS IN BRIDGE REPLACEMENT PROJECTS - Khoiri, Risma; Risma Dwi Admajayani; Trisno Widodo (Department of Civil Engineering, Faculty of Engineering, Universitas Islam Malang, 2023)
Bridge construction work is work that carries great risks. The research aims to determine the type and level of risk as well as risk control and the application of control methods to the Trisula Bridge Replacement Project. Based on the research results, various types of risks were identified and evaluated using the HIRADC approach and the JSA method. These risks are then assessed based on their level of likelihood and impact, and the risk level is determined. From the results of the risk identification carried out on the 10 main jobs for the Bridge Replacement Project, several jobs have moderate risk and high risk. Implementing risk control in the field is considered good for each job. However, to further improve efforts to prevent work accidents, it is necessary to pay attention to several things, namely checking the strength of the railing. In addition, it is important to continuously monitor and evaluate the implementation of risk controls in the field and ensure good awareness and understanding of risk control measures among workers. These efforts will help reduce risks that may arise during project implementation. Keywords: Risk; Occupational Safety and Health (K3); HIRADC; JSA; Bridge.